2014, No. 15, Table of Contents - Archyvas, Žurnalo (Buhalterinės apskaitos teorija ir praktika, 2018)
Financial accounting challenges Marta Lapková, Jana Stašová, Recognition of comprehensive income in Slovak companies, 8 Inga Bumane, Accounting policy in Latvia – existing main rules and current trends, 15 Neringa Stončiuvienė, Danutė Zinkevičienė, Comparative analysis of company performance result financial statements, 30 Birutė Gudonytė, Kristina Rudžionienė, The relationship between the financial crisis and the measurement of fair value in financial statements, 43 Ieva Vaičiulytė, Kristina Rudžionienė, Peculiarities of enterprise equity and equity accounting, 52 Corporate social responsibility and information disclosure Ramunė Budrionytė, The disclosure of information about organization social responsibility in financial statements: benefits and opportunities, 63 Inga Karlonaitė, Kristina Rudžionienė, Quality assessment model of environmental information disclosure, 76 Vytautė Petraškaitė, Kristina Rudžionienė, The disclosure of corporate social responsibility which is presented in the financial information on the internet, 88 Tomas Baležentis, Romualdas Valkauskas, The use of the farm accountancy data network for estimation of the optimal family farm size according to the microeconomic theory, 101 Tendencies of management accounting Marija Kučinskienė, Regina Jakiūnienė, The system of integrated activities evaluation – possibility for successful business processes management, 113 Daiva Tamulevičienė, Responsibility centres in the system of controlling, 126 Vilius Savickas, Julija Šarupičiūtė, Factors influencing the target costing process, 141